Discussion on the Meaning of “Reverie of Groups” During School Consultation - Yoshie Ohashi (Forum for Group Psychotherapies and Processes)
In schools, where teachers tend to seek immediate solutions, the question of how to provide meaningful interventions has drawn considerable attention from school psychologists all over the world. The purpose of the present study is to analyze case data, including the phenomenon named “reverie of groups” from a previous study, which refers to the retention of discomfort in a group of teachers, resulting in an indirect change in problematic students. In this case study, it was initially difficult to adopt a clear policy that created immediate solutions; the psychologist and teachers experienced feelings of uncertainty. After several consultations between the psychologist and teachers however, the troubled student indirectly changed. The teachers’ attitudes became responsive and pro-active in the aftermath. Thus, the significance of reverie in the school consultation context was demonstrated, as was the power of groups to maintain a sense of security by sustaining the capacity of reverie.